Europe and the World in Austria’s Policy in the Context of the 2013 Election to the National Council (Economic and Political Thought, 2014)
The author analyses the role of international issues in the policy of Austriafrom the perspective of the election to the National Council that took placeon 29 September 2013. The article presents the analysis of particular parties’approach to those issues, including the Social Democratic Party of Austria(Sozialdemokratische Partei Österreichs, SPÖ), the Austrian People’s Party(Österreichische Volkspartei, ÖVP), the Freedom Party of Austria (FreiheitlichePartei Österreichs, FPÖ), The Greens – The Green Alternative (Die Grünen –Die Grüne Alternative, GRÜNE), Team Stronach for Austria (Team Stronachfür Österreich, TS), NEOS – the New Austria and Liberal Forum (NEOS– Das Neue Österreich), and the Alliance for the Future of Austria (BündnisZukunft Österreich, BZÖ). The article describes the role of internationalorganisations in the contemporary policy of that country. Attention is drawnto the debate of that time on the participation of Austrian troops in the UNoperations. The role of history in the contemporary discourse on the Austrianforeign policy is also an important element. The issues connected with theattitude towards the Nazi past of the country are worth mentioning here inparticular.